2020
DOI: 10.1038/s41598-020-64299-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of acute type A aortic dissection in emergency departments

Abstract: Due to the symptoms, patients with acute type A aortic dissection are first seen by the ambulance service and diagnosed at the emergency department. How often an aortic dissection occurs in an emergency department per year has been studied. The incidence in the emergency department may be used as a quality marker of differential diagnostics of acute chest pain. A multi-institutional retrospective study with the municipal Berlin hospital chain Vivantes and its Department of Pathology and the Charité - Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 22 publications
1
41
1
1
Order By: Relevance
“… 1 2 4 5 In a rare previous Asian nationwide population-based study, Yeh et al 12 demonstrated that the annual incidence rate of AD was 5.6 per 100,000 person-years, and that the average annual incidence of patients treated surgically for type A AD was 1.44 per 100,000 person-years in Taiwan. Additionally, in a recent German multi-institutional retrospective study, Wundram et al 15 demonstrated that the emergency department incidence of acute type A AD was 5.24 per 100,000 person-years. However, this group only investigated the prevalence rate and did not address the treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 1 2 4 5 In a rare previous Asian nationwide population-based study, Yeh et al 12 demonstrated that the annual incidence rate of AD was 5.6 per 100,000 person-years, and that the average annual incidence of patients treated surgically for type A AD was 1.44 per 100,000 person-years in Taiwan. Additionally, in a recent German multi-institutional retrospective study, Wundram et al 15 demonstrated that the emergency department incidence of acute type A AD was 5.24 per 100,000 person-years. However, this group only investigated the prevalence rate and did not address the treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Because concurrent cocaine use is a relatively rare feature among all aortic dissection cases, patients could be misdiagnosed due to cardiovascular genesis being more likely associated to cocaine use [ 4 ] . In the history-taking setting of a patient with acute chest pain in the emergency room, the use of drugs should be included in the differential diagnostic considerations and the diagnosis of acute aortic dissection should be considered [ 8 , 24 , 25 ] .…”
Section: Discussionmentioning
confidence: 99%
“…In the International Registry of Acute Aortic Dissection (IRAD), cocaine use was reported in 1.8% of all cases [ 6 ] . Acute type A aortic dissection occurs at a population-based incidence ranging from 2.1 to 16.3 per 100.000 persons [ 7 , 8 ] . The European Union had about 513.5 million inhabitants in 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Acute type A aortic dissection (ATAAD) is one of the most dramatic life-threatening diseases with an incidence that may be significantly higher than previously assumed based on previous retrospective studies [1][2][3][4][5]. This is underlined by the fact that up to one-half of ATAAD cases are detected only at autopsy [5].…”
Section: Introductionmentioning
confidence: 97%
“…Acute type A aortic dissection (ATAAD) is one of the most dramatic life-threatening diseases with an incidence that may be significantly higher than previously assumed based on previous retrospective studies [1][2][3][4][5]. This is underlined by the fact that up to one-half of ATAAD cases are detected only at autopsy [5]. Accumulation of experience, development of diagnostic tools, and improved treatment strategies have resulted in improved results of surgical treatment over time: according to International Registry of Aortic Dissection (IRAD), operative mortality dropped over time from 25 to 18% [6].…”
Section: Introductionmentioning
confidence: 99%